INNOVATIONS IN HIGHER EDUCATION CLINICAL INSTRUCTOR TRAINING FOR OCCUPATIONAL THERAPY: A Program Evaluation - Haithcock, Tommianne (East Carolina University, 2020)
The purpose of this study is to evaluate a clinical instructor program model by using a program evaluation research design to determine best practices for an open access clinical instructor training program. Evaluating the clinical instructor training model will provide valuable information to help make judgements regarding the merit of the program. The literature review provides additional evidence supporting the need to evaluate a clinical instructor training model including: attributes of clinical instructors, clinical instructor performance, mastering the instructor role, key elements to develop a clinical instructor program, instruments to measure educator perceived confidence, adult learning theory, communication, evidence based practice, clinical judgment, demonstrating collegiality, teaching strategies for instructors, and fostering a positive environment for learning. An online survey format will be implemented with closed and open ended questions to collect responses incorporating a census of 100 with a randomized sample of 40 clinical instructors. Questions on the survey support the innovative strategies for clinical instructor training. User analytics will be collected from the Clinical Instructor Resource Website as a secondary data source to assist with identifying links that are of high priority to users. Data will be collected in an aggregate format with an analysis confirming the sufficiency of the Clinical Instructor Resource Website and best practice for clinical instructor training. Based on the results of this study, there is excellent potential to develop a clinical instructor training module in an open access online format. The results of this study can be shared with stakeholders in all health care fields.
Keywords: Clinical instructor/preceptor; Fieldwork/Clinical; Program evaluation; Teaching strategies, Adult learning theory; Communication; Collegiality; Training modules; Open access training; Medical education; Medicine--Study and teaching (Preceptorship)